1983
DOI: 10.1055/s-0038-1665245
|View full text |Cite
|
Sign up to set email alerts
|

ADP-Induced Platelet Release Reaction in Acute Stroke

Abstract: SummaryThe extent of the ADP-induced platelet release reaction has been determined in 107 patients admitted to hospital with acute stroke. In 43 of the patients a precise diagnosis was obtained and in those with proven thromboembolic stroke the mean extent of the release reaction was significantly higher than for those with either primary haemorrhagic stroke or those with subarachnoid haemorrhage. Enhanced platelet reactivity was also found in the patients in whom a precise diagnosis could not be obtained, mos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
17
0
2

Year Published

1984
1984
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(22 citation statements)
references
References 1 publication
3
17
0
2
Order By: Relevance
“…Bazı çalışmalarda İSK'nın nedeni olarak altta yatan trombosit fonksiyon bozukluğu suçlanmıştır (10)(11)(12). İSK'lı hastalarda trombosit fonksiyonlarını değerlendiren az sayıda çalışma olup bu çalışmaların sonuçları arasında çelişkiler bulunmaktadır (1,6,8).…”
Section: Discussionunclassified
See 1 more Smart Citation
“…Bazı çalışmalarda İSK'nın nedeni olarak altta yatan trombosit fonksiyon bozukluğu suçlanmıştır (10)(11)(12). İSK'lı hastalarda trombosit fonksiyonlarını değerlendiren az sayıda çalışma olup bu çalışmaların sonuçları arasında çelişkiler bulunmaktadır (1,6,8).…”
Section: Discussionunclassified
“…Mulley ve ark. tromboembolik inmeli hastalarda trombosit reaktivitesinde artış bulurken İSK'lı hastalarda ise trombosit reaktivitesinde azalmayı belirtmişlerdir (11). Mayda ve ark.…”
Section: Discussionunclassified
“…Others have recently reported that the ADP-induced platelet release reaction is reduced in persons with primary intracerebral hemorrhage -a disease strongly related to hypertension and involving the same vascular territory as lacunar infarction. 13 Nearly normal /3-TG values have also been noted in patients with hemorrhagic cerebrovascular disease.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies, including important early work by Mulley, Heptinstall and colleagues on ADP-induced platelet reactivity, have shown that platelets are excessively activated or hyper-reactive in the early [9][10][11][12][13][14], subacute [12] or late phases [10,11,13,14] after TIA or ischaemic stroke.…”
Section: Introductionmentioning
confidence: 99%